Cultural diversity and biodiversity as foundation of sustainable development - Y. Purwanto; Endang Sukara; Purity Sabila Ajiningrum; Dolly Priatna (Universitas Pakuan, 2020)
INTRODUCTION We know that there is only one earth, there are many different worlds. Different worldviews do not only have significant political and socio-economic repercussions but they also determine the way in which people perceive and interact with nature, thus forming their specific culture. Natural ecosystems cannot be understood, conserved and managed without recognizing the human culture that shape them, since biological and cultural diversities are mutually reinforcing and interdependent. Together, cultural diversity and biological diversity hold the key to ensuring resilience in both social and ecological systems (Erdelen, 2003). Through the environmental sciences and cultural activities, in promoting awareness and understanding of the relationships between biological and cultural diversity as a key basis for sustainable development.Beside has high biological diversity Indonesia also possesses high cultural diversity. It doesn’t marvel that Indonesia is the world’s largest archipelago, containing more than seventeen thousand island extending in an east-west direction for five thousand two hundred kilometers across the Sunda and Sahul continent shelves. The archipelago exhibits rich biodiversity that is unequalled in Asia (McNelly et al.,1990). Indonesia’s territory cover 7.7 million square kilometer, of which approximately 5.8 million square kilometers (75.3 %) is comprised of marine and coastal waters. Indonesia is located between two of Earth’s biogeographic regions: Indo-Malaya and Oceania. The Indo-Malaya region to the west includes Sumatra, Kalimantan, Java, and Bali, and the Oceanic region to the east includes Sulawesi, Moluccas, the eastern Sunda Islands, and West Papua. The vegetation types to the east and the west of the Wallace line are divided by a biogeographical boundary that extends from north to south along the Sunda Shelf. The natural vegetation on the shelf it self is comprised principally of the Malesian type, dominated by the commercially important Dipterocarpaceae. Vegetation to the east has greater affinities with Oceanic Austro-Pacific zone and is dominated by mixed tropical hardwood species. Deciduous monsoon forest occurs in seasonally dry areas, particularly in the southern and eastern islands such as the Lesser Sunda and the southern part of Papua. The outer islands of Sumatra, Kalimantan, Sulawesi, Moluccas, and Papua comprise approximately 10 % of the world’s tropical rainforest. Indonesia has more tropical forest than any other single Africa or Asia country, and is second only to Brazil in terms of tropical forest area. This country characterized by an enormously varied topography of shallow coastal water, swamp, lakes, alluvial plains, volcanoes, and High Mountain ranges. This country also presents at least forty-seven distinct natural and man-made ecosystems. These ecosystem types ranges from the ice mountain ecosystem and alpine grassland on the high mountains in Papua (Puncak Jaya Wijaya, at an altitude of over five thousand metres0 to variations of tropical rainforest ecosystems– from lowland to mountain landscape, shallow swamp to deep lakes, from mangroves to algae communities and coral reefs – as well as an ocean ecosystem reaching as deep as eight thousand meters below sea level (MoF/FAO, 1991).Unfortunately, little respect has been given to the high diversity of the archipelago, resulting in disappearance of many of these cultures. Studies to document and learn traditional wisdom are needed urgently, not least because traditional knowledge is often compatible with sustainable development objectives, as discussed in the World Summit on Sustainable Development, in Rio de Janeiro, 1992 and in Johannesburg in 2002. Meanwhile the deforestation in Indonesia occurs at an alarming rate. Forest cover decreased from about 193.7 million hectares in 1950s (Hannibal, 1950) to 119.7 million hectares in 1985 and to 100 million hectares in 1997 (GOI/World Bank, 2000) and only 98 million hectares remain (FWI/GWF, 2001).The local knowledge of environment management and indigenous custom, as part of indigenous culture, is the product of long interaction between man and their environment and also results of their ability for application the technique adaptation to their environment. High biological diversity has utilized for economic reason, even though this national asset has not yet been fully developed.Dynamic interaction between people and biodiversity in Indonesia let to the creation of many different cultures and thus languages and dialects. More than four hundred Indonesian ethnic groups are dispersed in different regions. Indonesia boasts665 different languages and dialects, with Papua accounting for 250 of these, Moluccas 133, Sulawesi105, Kalimantan 77, Nusa Tenggara (Lesser SundaIslands) 53, Sumatra 38, Java and Bali 9 (Grimes,1988). Such ethnics have specific knowledge about how to manage their environment and biodiversity surrounding them. Every ethnic has a specific culture, knowledge and local wisdom and technique adaptation to their various environments.Concerning the cultural richness in Indonesian, besides have advantages also constitute weaknesses for biodiversity resource management. One of these advantages is that we have various referable traditional pattern and alternative selection of space management and we have material to design system admissible management by all societies and also government. Meanwhile its weakness is that each ethnic has specific pattern according to environmental condition and cultural level. But along with time developing marks sense decentralization of policy in Indonesian, therefore local or region policy that based on actual condition area and society is more elegant compared with uniformity management which hasn’t obviously fastened byother area that has different culture and environmental condition.